Bringing Clarity to Transformative Learning Research - Chad Hoggan (Adult Education Research Conference, 2015)
This paper presents the results of a review of the literature on transformative learning theory that focused on transformational outcomes. The wide variety of outcomes present in the research literature are organized into a typology, and recommendations are made for future scholarly work using the theory.
Keywords: Transformative learning; learning outcomes; theory development